The laborious designing of the past (Bulletin KNOB, 2006)
Dealing correctly with the built past is the key question of each individual case of preservation of monuments and historic buildings. After all, a thorough refurbishment inevitably implies a form of intervention in the 'natural' course of history. At the same time the final result of not doing anything, often implies that eventually nothing is left. However, once a drastic restoration has been decided on for that reason, it is tempting to do more than what is strictly necessary for preservation: removing annoying additions from earlier centuries, eliminating previous restorations, perfectioning the object aesthetically by making it stylistically uniform. Thus falsification of history sometimes threatens, because a building is made to look 'old'.In this article five categories of such deliberate designing of the past are distinguished. The first relies on a frequently commercially inspired nostalgia. Long lost buildings that nobody is acquainted with anymore are newly erected for the sake of an intended historical image, such as the planned donjon of the Valkhof in Nijmegen. The second group concerns reconstruction in the old style after acts of war or fire damage, in an attempt at restoring destroyed national heritage that everyone has been acquainted with: the Lakenhal in Ieper. However, the longer this is postponed, the more forced the restoration becomes.In the third group the intervention is more fundamental. Not repair of damage is the motive, but the deliberate reconstruction of a specific phase of a monument, while anything incompatible with this is purged out: palace Het Loo. Such a reconstruction can be so drastic that in practice the boundary between historical reliability and historical fiction is exceeded, as in Cuypers's approach to the Munster church in Roermond. Often this is also (partly) based on political ideological motives: a specific past is required in the present. One step further and we are in category five: the use of this historical fiction as a starting point for new buildings, which are legitimised by this historical fiction, such as the Karlskirche in Vienna, the layout of which was based on an incorrect reconstruction of the Temple of Solomon in Jerusalem.